The Mechanisms of Traditional Chinese Medicine Underlying the Prevention and Treatment of Parkinson's Disease - Li, Xiaoliang; Zhang, YaNan; Wang, Yu; Xu, Jing; Xin, Ping; Meng, YongHai; Wang, Qiuhong; Kuang, Haixue (Frontiers in Pharmacology, 2017)
Parkinson’s disease (PD), characterized with bradykinesia, static tremor, rigidity and disturbances in balance, is the second most common neurodegenerative disorder. Along with the largely aging population in the world, the incidence is increasing year by year, which imposes the negative impacts on patients, their families and the whole society. Traditional Chinese medicine (TCM) has a good prospect for the prevention and cure of PD due to its advantages of less side effects and multi-targets effects. At present, the pathogenesis of PD is not yet fully discovered. This paper elaborate the mechanism of TCM underlying the prevention and treatment of PD with regards to the inhibition of oxidative stress, the regulation of mitochondrial dysfunction, the reduction of toxic excitatory amino acids (EAA), the inhibition of neuroinflammation, the inhibition of neuronal apoptosis, and the inhibition of abnormal protein aggregation.